Supply chain management for refurbishment lessons from high street retailing - Male, Steven (Thomas Telford, 2003)
This is a practical volume that combines all of the issues faced when dealing with refurbishment and addresses all of the roles invlolved. It is the outcome of a three-year research project involving seven major high street retailing clients.